A probable genetic origin for pitting enamel hypoplasia on the molars of Paranthropus robustus. Issue 129 (April 2019) - Towle, Ian; Irish, Joel D.
Abstract: We report the frequencies of linear enamel hypoplasia (LEH) and, specifically, pitting enamel hypoplasia (PEH) defects in the teeth of Paranthropus robustus, for comparison with four other South African hominin species and three extant nonhuman primate species. Unlike LEH, the lesser known PEH is characterized by multiple circular depression defects across a tooth crown and is often difficult to interpret in terms of developmental timing and etiology. Teeth in all samples were examined macroscopically with type, position and number of defects recorded. Frequencies of teeth with LEH vary among hominin species, but the differences in PEH are considerable. That is, P. robustus has much higher rates of pitting defects, with 47% of deciduous teeth and 14% of permanent teeth affected, relative to 6.7% and 4.3%, respectively, for all other hominin teeth combined; none of the extant primate samples evidences comparable rates. The defects on P. robustus molars are unlike those in other species, with entire crowns often covered in small circular depressions. The PEH is most consistent with modern human examples of amelogenesis imperfecta. Additionally, the defects are: 1) not found on anterior teeth, 2) uniform in shape and size, and 3) similar in appearance/severity on all molars. Therefore, this form of PEH may have been a side effect of selection on another trait that shares the same coding gene(s), i.e., these defects have a genetic origin. We discuss a possible scenario that may explain how this form of PEH evolved to become so common in the Paranthropus genus.